Influence of Product Price and Shopping Convenience on Consumer Satisfaction - Warni, Zahra Sukma; Sari, Aida; Ambarwati, Dwi Asri Siti (Journal of Business Management and Economic Development, 2025)
Retail business competition is getting tighter, so understanding consumer satisfaction factors is very important. This study aims to determine the effect of product prices and shopping convenience on consumer satisfaction at Al Amin Multimart Store. Competitive product prices and shopping convenience are consumers’ main considerations when determining where to shop. This study uses a quantitative method with a causal associative approach. Data were collected by distributing questionnaires to 110 respondents who are consumers of Al Amin Multimart Store. The data analysis technique used is multiple linear regression to measure the effect of independent variables, namely product prices (X1) and shopping convenience (X2), on the dependent variable, namely consumer satisfaction (Y). The study results indicate that product prices and shopping convenience positively and significantly affect consumer satisfaction. This means that the more competitive the product price is and the more comfortable the shopping experience is, the more consumer satisfaction increases. Therefore, Al Amin Multimart Store is advised to maintain a competitive pricing strategy and improve facilities and services to create a better shopping experience.